2008
DOI: 10.1258/td.2007.060177
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of pleural empyema and associated factors with prolonged hospitalization in paediatric tertiary centre in Angola, Luanda

Abstract: In a case series of 152 children aged from 2 to 132 months will pleural emphema from a paediatric tertiary hospital in Luanda, Angola between September 2004 and March 2005, the authors found a high prevalence of anaemia and malnutrition. The most prevalent bacteria in pleural fluid were: D pneumoniae, Haemophyllus and S aureus. The median for hospital stay was 25 days. The lethality was 7.8% and was not statistically associated with malnutrition, although this variable was associated, in multivariate analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…Thus, patients with fever, coughing, tachypnea and radiological changes were diagnosed with pneumonia, and those with subcostal recession were classified with severe pneumonia. In our casuistic, factors such age, anorexia, sibilance, difficult breathing, and vomiting were statistically correlated with pneumonia severity what corroborates with other studies [30, 3336]. Presence of abdominal pain in children with pneumonia was observed by us as reported by other authors, but without any association with the disease severity [34, 37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, patients with fever, coughing, tachypnea and radiological changes were diagnosed with pneumonia, and those with subcostal recession were classified with severe pneumonia. In our casuistic, factors such age, anorexia, sibilance, difficult breathing, and vomiting were statistically correlated with pneumonia severity what corroborates with other studies [30, 3336]. Presence of abdominal pain in children with pneumonia was observed by us as reported by other authors, but without any association with the disease severity [34, 37].…”
Section: Discussionsupporting
confidence: 91%
“…Anemia has a high prevalence in our midst, as demonstrated by Carvalho et al, who found a prevalence of 92% of healthy children in day care centers in the public health network with hemoglobin levels < 11.0 g/dL; but it was not also associated to severe pneumonia [12, 38]. The elapsed time between the beginning of the disease and its diagnostic, which can be related to the difficult access to the health services, was associated with disease severity, corroborating with other studies carried out in Brazil and Africa [33, 39]. Coincidently, all children under 5 years old were from countryside and presented severe pnuemonia.…”
Section: Discussionsupporting
confidence: 73%